Stage-specific screening reveals differential resilience response to cold stress in rice - Fahamida Akter; Partha S. Biswas; Abul Kalam Mohammad Aminul Islam; Mohammad Sharif Raihan; Md. Mizanur Rahman; Khandakar Md. Iftekharuddaula; Mohammad Rafiqul Islam; John Damien Platten (PLoS ONE, 2026)
Rice cultivation in the northern and northeastern districts of Bangladesh faces cold stress during the seedling and reproductive stages that drastically reduces yield. As a precursor to generate improved elite lines, a diverse panel of rice germplasm was screened to identify genotypes with resilience to low temperature at both key developmental phases. Seedling-stage tolerance was assessed using an artificial cold-water tank, while reproductive-stage cold tolerance was evaluated under both natural field conditions and controlled cold screening facilities. Two breeding lines - BR8907-B-1–2-CS1–4-CS2-P3-4 and BR8909-B-12–2-CS1–4-CS2-P2-3–2, demonstrating minimal leaf discoloration and the highest survival rates, and lacking the known QTL ( qSCT1 ) for seedling stage cold tolerance indicated contributions from other QTLs or genetic factors. Five genotypes (Bhutan, IR83222-F11-173, Rata Boro, BRRI dhan74, BR11712-4R-227) showed tolerance at the reproductive stage, while three lines (Bhutan, BR11712-4R-227, and BR12266-44-11-32-5-1-1-HR10-B) showed moderate tolerance at both seedling and reproductive stages, indicating stage-specific responses. The genotypes BR10317-5R-25, IR18A1859, and BRRI dhan28 were consistently susceptible at both stages. Principal Component Analysis (PCA) indicated that seedling and reproductive traits contributed jointly to variation under field conditions but independent under controlled environments, reflecting stage-specific genetic regulation. These findings highlight the complex, stage-dependent nature of cold tolerance and the importance of stage-specific screening to inform effective breeding strategies for enhanced cold resilience in rice.